A Study on Design of Micro-Hydropower Plant for Run-off Water Sources in Bangladesh (IUBAT Review, 2024)
Hydropower has been one of the most used energy sources in the world since historic times. Electricity production from hydropower has been there for decades, particularly in isolated regions. Studies have shown that 232 rivers in Bangladesh can be used for micro-hydropower generation and energy security for isolated communities with a reasonable flow rate. The run-off water from these rivers can be used as a clean energy source for running micro-hydro power plants. The main objective of this study was to investigate and justify the potentiality of micro-hydropower in Bangladesh and design a cross-flow turbine to harness power from these rivers. This study considered several design considerations, and a theoretical analysis was performed to create a cross-flow turbine. Then, a turbine was developed, and numerical analysis was conducted using ANSYS-CFX software. Results show that the turbine can achieve a peak efficiency and shaft power of 84.60% and 4.68 kW, respectively. Results indicated that a site with 100-150 liter/s of flow rate and a head of 5-6 meters could easily produce around 3-5 kW of power supply, considering all kinds of losses. The current study is expected to provide helpful information for improving hydropower-based electricity generation in Bangladesh.IUBAT Review—A Multidisciplinary Academic Journal, 7(2): 30-43